Pembelajaran Materi Bangun Datar Pada Siswa SD Kelas IV Dengan Menggunakan Pendekatan Konstruktivisme - Puspita, Yanti; Ristiana, Muhammad Ghiyats (IKIP Siliwangi, 2020)
The research aims to analyze (1)scenarios and implementation constructivism approach, (2) the response of teachers and students, (3) The difficulties experienced by students in complete a task. The subject of this research are 15 students of fourth (IV) grade of SDN Palintang Jaya. 5 Students high level, 5 Students middle, 5 students low level. This research is a qualitative methods. The scenario and point to finding froms the students can more active teacher lesson learned by means of concrete using media and social interaction between teachers or friends. A good response from teachers and students. The difficulties experienced by students in complete a task, because the students are still unable to use mathematics concept. Based on the result of this research shows that reach mathematical understanding ability, after following construtivism approach.